Effects of a Television and Radio Advertising Ban: A Study of the Cigarette Industry - HOLAK, Susan L. (Institutional Knowledge at Singapore Management University, 1986)
By using the cigarette industry's ad ban of 1970 as a "natural" experiment, the authors explore mana- gerially related effects of such an advertising "shock" through price and advertising elasticities as well as brand purchase inertia. Results indicate substantial differences in the elasticity and inertia values be- tween pre- and post-ban periods. In an environment with reduced advertising options, product demand is more price sensitive. Demand also becomes more inelastic with respect to advertising fluctuations if television and radio can no longer be used as media vehicles. Brand purchase inertia is significantly higher after the ban as consumers cease to learn of and experiment with new brands. The study has important implications for brand management in a regulatory setting and addresses the possibility of an advertising ban's potential to act as a barrier to entry.